Potensi Pengembangan Crowdfunding Syariah sebagai Alternatif Pembiayaan Sosial di Era Digital - Laeliyah, Rizka; Vidiati, Cory (SENTRI: Jurnal Riset Ilmiah, 2025)
The rapid advancement of digital technology has fostered innovation in the financial sector, notably through the emergence of crowdfunding as an alternative model for social financing. This study analyzes the potential development of Islamic crowdfunding as an inclusive and Sharia-compliant social financing instrument in the digital era. Using a qualitative method with a literature study approach, the research draws on secondary sources including academic journals, regulatory documents, and reports from Islamic financial institutions. The findings reveal that Islamic crowdfunding offers substantial potential in promoting financial inclusion, supporting community economic empowerment, and contributing to the achievement of Sustainable Development Goals (SDGs), particularly in reducing poverty and improving welfare. This research contributes by highlighting the strategic role of Islamic crowdfunding in bridging the gap between social finance and technological innovation within an Islamic framework. However, several challenges persist, such as the absence of comprehensive regulations, limited Islamic financial literacy, and concerns over data security and public trust. To address these issues, an integrated strategy is proposed through regulatory strengthening, Sharia certification, collaboration with Islamic social institutions, and the adoption of blockchain-based innovations accompanied by digital literacy enhancement. Through the synergy of regulators, financial institutions, and society, Islamic crowdfunding can evolve into a key driver of a fair, transparent, and sustainable social finance ecosystem in Indonesia.